Analisis Tantangan dan Peluang dalam Transformasi Metode Pembelajaran PAI Berbasis Teknologi pada Abad 21 - Muhammad Saripuddin B (Khazanah : Journal of Islamic Studies, 2025)
This study aims to analyze the challenges and opportunities in the transformation of Islamic Religious Education (PAI) teaching methods through the integration of digital technology in the 21st century. Using a qualitative descriptive approach, the research was conducted through in-depth interviews, observations, and documentation involving PAI teachers, school principals, and students in several secondary education institutions. The findings reveal that while digital-based PAI instruction offers promising opportunities, such as increased student engagement, access to diverse learning resources, and the potential for collaborative and creative learning, it also encounters significant challenges. These include limited digital literacy among teachers, unequal infrastructure access, resistance to pedagogical change, and difficulties in integrating spiritual values through digital platforms. However, the study also highlights a growing enthusiasm among students and young teachers for digital tools, as well as emerging practices such as Islamic content creation and online professional learning communities. The study concludes that successful transformation requires strengthening teacher capacity, equitable infrastructure development, curriculum reform, and strategic institutional support to ensure that technology-enhanced Islamic education remains pedagogically sound, value-oriented, and responsive to the demands of the digital era.